Perlindungan Hak Asasi Manusia Dalam Konsep Pembatasan Usia Pernikahan Pada Uu No 16 Tahun 2019 - Ainullah Ainullah (ASASI: Journal of Islamic Family Law, 2021)
The protection of human rights has a guarantee from the legal system in Indonesia. The Marriage Age Restriction regulated in Law No. 16 of 2019 is a new rule as a form of revision to natural rules. The latest regulation states that the age of marriage is nineteen years for both the prospective husband and the prospective wife. The results of the analysis show that the state has protected the rights of every citizen who wants to get married. Although the regulation has been promulgated through a new regulation, the state is still present in order to fulfill aspects of human rights, one of which is by enforcing marriage dispensation rules, for anyone who wants to marry under the age of marriage.